2005
DOI: 10.1088/0953-8984/17/30/007
|View full text |Cite
|
Sign up to set email alerts
|

Absence of the 90 K structural transition in CuV2S4crystals grown by chemical vapour transport using TeCl4

Abstract: Various physical properties (magnetization, specific heat, optical reflectance, electrical resistivity) of CuV 2 S 4 crystals grown by chemical vapour transport using TeCl 4 as the transporting agent have been measured. The data show slight differences compared to samples grown using different techniques. These differences include the absence of a sharp drop in magnetization and the absence of a peak in the heat capacity near 90 K. These differences suggest that the cubictetragonal phase transition near 90 K d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 25 publications
2
10
1
Order By: Relevance
“…Figure 11a-c show the temperature dependence of the susceptibility at applied magnetic fields of 400 G, 1 kG, and 1 T, respectively. It is found that the weak spike-like susceptibility appearing in the region of about 80 K to 90 K reduces gradually with increasing applied magnetic filed, and disappears at 1 T. The susceptibility curve at 1 T is very simi- T(K) lar to those obtained at applied magnetic fields of 1 T, 3 T, and 5 T for single crystals reported by Crandles et al [7]. From the present investigations of the susceptibility, we deduce that the spike-like susceptibilities appearing in the region of about 40 K to 55 K and of about 80 K to 90 K depend on the specimen -type of fine powders, crystals, and single crystal -in addition to the spatial alignment between the crystallographic axes and the applied magnetic filed.…”
Section: (C)supporting
confidence: 53%
See 4 more Smart Citations
“…Figure 11a-c show the temperature dependence of the susceptibility at applied magnetic fields of 400 G, 1 kG, and 1 T, respectively. It is found that the weak spike-like susceptibility appearing in the region of about 80 K to 90 K reduces gradually with increasing applied magnetic filed, and disappears at 1 T. The susceptibility curve at 1 T is very simi- T(K) lar to those obtained at applied magnetic fields of 1 T, 3 T, and 5 T for single crystals reported by Crandles et al [7]. From the present investigations of the susceptibility, we deduce that the spike-like susceptibilities appearing in the region of about 40 K to 55 K and of about 80 K to 90 K depend on the specimen -type of fine powders, crystals, and single crystal -in addition to the spatial alignment between the crystallographic axes and the applied magnetic filed.…”
Section: (C)supporting
confidence: 53%
“…9a, the susceptibility does not show any large modulation at 50 K and 90 K and smoothly decreased on heating, while Fig. 9b shows two small modulations at about 55 K and 90 K. However, the susceptibility reported by Crandles et al [7] gradually increased on heating above about 70 K. For comparison, at 80 K and 1 T, the susceptibility is about 4.78 × 10 −6 emu/gOe in Fig. 9.…”
Section: Experimental and Resultsmentioning
confidence: 74%
See 3 more Smart Citations